Innovation in Education Policy at Nurul Musthofa Islamic Boarding School - Setiawan, Bagus; Erwanto, Angga; Ningsih, Dinah Zahra Restia; Nadela, Nadela; Aisyah, Nadia; Heri, Rif’at Reza Ramadhan; Fitria, Saripatul (Educational Journal of Learning Technology, 2024)
This research aims to determine the educational policies at the Nurul Musthofa Islamic Boarding School. This research uses qualitative research. Qualitative research contains complex images, examines words, and provides detailed reports from respondents' views. It also conducts research in natural situations. The research results explain that the vision and mission of the Nurul Musthofa Islamic boarding school, in general, cannot be separated from the superiority of this Islamic boarding school, which prioritizes the Tahfidz program. Takhassus Al-Qur'anul Karim, Amtsilati, and Nurul Mustofa Ekselensia are the flagship programs at this Islamic boarding school. Integrating religious knowledge and general knowledge is a characteristic of the Nurul Musthofa Islamic boarding school. Cultivating noble moral traits starts from the example given by the ustadz-ustadzah. The Islamic boarding school always evaluates the implementation of activities at the school.